Influence of the storage period on the nutritional and microbiological value of sun-dried brewer’s grains - Faccenda, Andressa; Zambom, Maximiliane A.; Avila, André S.; Castagnara, Deise D.; Dri, Ricardo; Fischer, Maria L.; Tinini, Rodrigo C. R.; Dessbesell, Jéssica G.; Almeida, Ana-Ruth E.; Almeida, Kleves V. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Brewer's grains, a by-product of the brewery industry, can be included in the diet of ruminants. However, its high humidity makes it difficult to store and preserve. Objective: To evaluate the efficiency of sun dehydration of wet brewer’s grains (WBG) and the effect of storage period on its nutritional and microbiological quality. Methods: A completely randomized experimental design was used to evaluate WBG dehydration efficiency, with treatments corresponding to 0, 1, 2, 4, 6, 8, 10, 12, 14 and 16 hours of sun exposure. A second experiment was carried out using also a completely randomized design to evaluated the effect of storage with the following treatments: 0, 10, 20, 30, 60, 90, 120, 150 and 180 days of storage of the dry by-product. Results: Dry matter (DM) content linearly increased with dehydration period. The chemical composition of the dried brewer's grains had no effect as a function of storage period. Indigestible protein (C fraction) increased linearly but did not compromise the cumulative gas production and the in vitro digestibility of DM and protein. Storage time had no effect on fungus population. The maximum aflatoxin value was 45.5 μg/kg, and remained within acceptable limits for bovine feed. Conclusion: Dehydration of WBG in the sun is efficient to guarantee conservation and makes it possible to store the by-product. The storage of the dry by-product for 180 days does not compromise its nutritional or microbiological quality.